Políticas públicas em energias renováveis e a bioeletricidade florestal brasileira: evidências empíricas para uma economia circular - Nunes, Anna Manuella Melo (2021)
The imminent depletion of fossil reserves, the growing global energy demand and the need to comply with environmental policies to combat greenhouse gas (GHG) emissions have led to an increase in the use of renewable energy sources in the global energy matrix. A systemic transition to more efficient energy regimes requires a strategically designed sequence of actions involving all levels of policy. Among the different approaches to achieving sustainable development is the circular economy, applied to renewable energies, in particular the bioeconomy. The objective of this research is to analyze the impacts of public policies on renewable energy and the structural evolution of Brazilian forest bioelectricity from a circular economy perspective. The data used were from plants participating in the Incentive Program for Alternative Sources of Electric Energy (PROINFA) and from forest biomass thermoelectric plants, through the Aneel Generation Information System (SIGA) of the National Electric Energy Agency (ANEEL). To achieve the objectives, a systematic review of the taxonomy of Public Policies (PP) was carried out, as well as the main sources, beneficiaries and convergences of circularity associated with PP for renewable energy. An ex-post and ex-ante analysis was also carried out, based on the econometric model of Diff-in-Diff to measure the impact of PROINFA's public policy in Brazil; finally, a descriptive analysis of the forest bioelectricity thermoelectric plants and their classification in relation to the assumptions of the circular economy was carried out. Among the results obtained, it was noted a scenario of energy development in the last 20 years and the application of circularity concepts observed in publications of the last 5 years. However, the review articles, which are essential for evaluating the policies implemented so far, are presented in a smaller quantity, and there is an opportunity to carry out comparative research. Regarding PROINFA, there was an increase of 10% in per capita income in the participating municipalities, 13.82% in the number of formal workers and 0.39% in capital expenditure, demonstrating that those benefiting from the program achieved economic development and Social. The analyzes carried out showed that PROINFA collaborated with regional development. From the circularity analysis, it was identified that the thermoelectric plants that use Black Liquor and Forest Residue presented a greater amount of circular economy premises in their production processes. It was also verified that they have operations in the international market, which evidenced the commitment to comply with the circular practices and the COP 21 goals. Those results can support a greater development of circular economy premises on the forest bioelectricity sectionneed for investments and public policies aimed at the circular economy.